Cyclic response of additive manufactured 316L stainless steel: The role of cell structures. (December 2021) - Cui, Luqing; Jiang, Fuqing; Deng, Dunyong; Xin, Tongzheng; Sun, Xiaoyu; Mousavian, Reza Taherzadeh; Peng, Ru Lin; Yang, Zhiqing; Moverare, Johan
Abstract: We report the effect of cell structures on the fatigue behavior of additively manufactured (AM) 316L stainless steel (316LSS). Compared with the cell-free samples, the fatigue process of fully cellular samples only consists of steady and overload stages, without an initial softening stage. Moreover, the fully cellular sample possesses higher strength, lower cyclic softening rate and longer lifetime. Microscopic analyses show no difference in grain orientations, dimensions, and shapes. However, the fully cellular samples show planar dislocation structures, whereas the cell-free samples display wavy dislocation structures. The existence of cell structures promotes the activation of planar slip, delays strain localization, and ultimately enhances the fatigue performance of AM 316LSS. Graphical abstract: Image, graphical abstract